Life Cycle Inventory and Assessment Datasets on the Operational Sustainability of the Ammonia Process - Sadeek, Sherard (Data Brief, 2020)
This article presents data affiliated with life cycle inventories, environmental impact and operational sustainability used in, the influence of raw material availability and utility power consumption on the sustainability of the ammonia process [1]. Scenario specific operating conditions were used to simulate the ammonia process based on unique constraints occurring within the Trinidad and Tobago energy sector. The data was collected using AspenⓇ Plus simulations and validated against plant operating data. The data consists of an economic cost evaluation as well as environmental impact using the CML-IA Baseline midpoint approach. The data was derived from life cycle inventories aligned to input/output material and energy flows within the ammonia process as well as life cycle assessment databases utilizing Ecoinvent v3.4. The data can be applied to the wider ammonia supply chain, aiding in achieving greater sustainable development within ammonia-based process industries.